Eksploracja dziedzictwa kulturowego w aspekcie rynkowych zastosowań kodów kulturowych - Paprocki, Rafał (Studia Etnologiczne i Antropologiczne, 2012)
The article concerns cultural heritage in terms of identifying cultural codes with their market applications. The very subject-matter is presented in the context of modern socio-civilizational changes. The leading premises of the studies on culture in the light of the market applications of cultural codes are the strengthening process of permeating the world of culture and the world of market, as well as the phenomenon of globalization. The article is based on the assumption that understanding the nature of modern cultural changes needs a multidisciplinary approach. In order to define the conditions of cultural and consumerist patterns three selected conceptions included in qualitative market studies were taken into account. After bringing the premises of a qualitative method closer, methods and techniques constituting the tools of the research on attitudes and preferences culturally-conditioned were discussed. The text closes with an attempt to reflect on the role of science and studies on cultural conditions of behaviours in terms of chances and threats deriving from the exploration of cultural heritage.